Single and multi-view 2D image processing for enhanced 3D object reconstruction - Ghosh, Swapnil; Mahmud, Md. Muhtasim; Ahmed, Asrar; Turjo, Tashdid Al Shafi; Salim, Md. Shaeak Ibna (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.